Skyrmion-Antiskyrmion Racetrack Memory in Rank-One DMI Materials - Hoffmann, Markus; Müller, Gideon P.; Melcher, Christof; Blügel, Stefan (Frontiers in Physics, 2021)
Chiral magnetic skyrmions, localized and topologically protected vortex-like magnetic textures that can be found in chiral magnets, are currently under intense study as an entity for information storage and processing. A recent study showed that so-called rank-one materials can host both skyrmions and antiskyrmions at the same energy. In such systems the Dzyaloshinskii-Moriya interaction, in general a tensorial quantity, is reduced to only one non-zero component. The presence of both skyrmions and antiskyrmions allows for the investigation of the possible interplay between them. Here, we investigate the stability and interaction of skyrmions and antiskyrmions as well as their transport properties subject to spin-orbit torque for a model system described by an atomistic spin-lattice Hamiltonian employing the simulation software Spirit. The spin-orbit torque driven spin-dynamics described by the Landau-Lifshitz Gilbert equation is compared to the effective one of the Thiele equation. We demonstrate that, even though skyrmions and antiskyrmions can be seen as antiparticles, a rather dense arrangement of both along a memory track is possible, enabling their use as representations of the binary data bits "0" and "1" in a memory device.